Kick double poling technique - factors distinguishing between skill levels in elite cross-country skiers - Lindinger, S.; Müller, E.; Göpfert, C.; Stöggl, T.; Holmberg, H. C. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Kick double poling (DPK) is considered a highly demanding classic skiing technique (uphill; 2-4°). The complex coordination of alternating pole and leg push-offs, swing and gliding phases highly demands the skiers' coordinative skills. Compared to DP or DIAG, DPK is less practiced in training and racing, especially in sprint, showing high potential in more efficient use and improvement of this skill. In contrast to DP and DIAG (i.e. Lindinger et al. 2009a/b; Stöggl et al. 2009), there is coaches' experience but little evidence about factors determining the quality of DPK, thus this pilot study aimed to compare biomechanical characteristics among different skill levels.